Improving the efficiency of agricultural entrepreneurship by processing rapeseed to biodiesel. - Humeniuk, Mariana; Nemish, Dmytro; SHELENKO, Diana; Balaniuk, Ivan (My University, 2021)
The expediency of rapeseed processing and biodiesel production is investigated in the article. Potential opportunities for biodiesel production at completed mini-plants have been identified and the costs for the creation of production facilities have been calculated. A comparative evaluation of the efficiency of biodiesel production from rapeseed and sale of its seeds has been carried out. Higher economic efficiency from rapeseed processing than mass export of this raw material is substantiated, which will increase the profitability of agricultural enterprises. The key guidelines for the location of production facilities for the processing of rapeseed for biodiesel on a cooperative basis at the regional level have been formed. The paper uses general and special research methods, in particular the calculation and design method to substantiate the estimated cost of production facilities for processing rapeseed into biodiesel. The results of interviews with key stakeholders, producers of rapeseed, prove the feasibility of practical application of these proposals in enterprises.
Keywords: agricultural enterprises, biodiesel, rapeseed processing